2009
DOI: 10.1038/sj.bjc.6604978
|View full text |Cite|
|
Sign up to set email alerts
|

Extracellular, cell-permeable survivin inhibits apoptosis while promoting proliferative and metastatic potential

Abstract: The tumour microenvironment is believed to be involved in development, growth, metastasis, and therapy resistance of many cancers. Here we show survivin, a member of the inhibitor of apoptosis protein (IAP) family, implicated in apoptosis inhibition and the regulation of mitosis in cancer cells, exists in a novel extracellular pool in tumour cells. Furthermore, we have constructed stable cell lines that provide the extracellular pool with either wild-type survivin (Surv-WT) or the previously described dominant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
163
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 132 publications
(172 citation statements)
references
References 39 publications
(49 reference statements)
7
163
0
2
Order By: Relevance
“…Uptake of Survivin by malignant cells has been shown to increase their proliferative rate [34]. To determine if Survivin uptake has a similar effect on T cells, we analyzed their proliferation using the cell-cycle-associated nuclear antigen Ki-67 [38], CFSE staining and BrdU incorporation.…”
Section: Survivin Uptake Results In Diminished T Cell Proliferationmentioning
confidence: 99%
See 4 more Smart Citations
“…Uptake of Survivin by malignant cells has been shown to increase their proliferative rate [34]. To determine if Survivin uptake has a similar effect on T cells, we analyzed their proliferation using the cell-cycle-associated nuclear antigen Ki-67 [38], CFSE staining and BrdU incorporation.…”
Section: Survivin Uptake Results In Diminished T Cell Proliferationmentioning
confidence: 99%
“…Recent studies have demonstrated that uptake of Survivin by cancer cells leads to a more aggressive phenotype [34]. To determine if tumor-infiltrating T cells would also be able to take up tumor-released Survivin, FLAG-HA-tagged Survivin was collected from cancer cell culture medium using dualaffinity purification and added to T cell cultures.…”
Section: T Cells Take Up Tumor-released Survivinmentioning
confidence: 99%
See 3 more Smart Citations